The influence of thickness, interpore distance and compositional structure on the optical properties of self-ordered anodic aluminum oxide films. Issue 32 (1st August 2016) - Manzano, C. V.; Best, J. P.; Schwiedrzik, J. J.; Cantarero, A.; Michler, J.; Philippe, L.
Abstract : The reflectance was found to depend on the thickness of the AAO films and significantly on the inter-pore distance (pore density). The chemistry of the system plays an important role regarding the optical properties. Abstract : Highly ordered anodic aluminum oxide (AAO) films were fabricated using a two-step anodization process in oxalic acid, sulfuric acid, or ethylene glycol containing sulfuric acid, which are important in design of nanostructured optical devices. The morphology and UV-Vis reflectance spectroscopy of these films were analyzed. The morphological parameters of the AAO films, such as the thickness, pore diameter, interpore distance, porosity, pore arrangement regularity, and anodization electrolyte, were adjusted in order to study the effect of these parameters on the UV-Vis reflectance properties of these films. Raman spectroscopy measurements were then utilized to better understand the chemical differences between the films. The reflectance was found to depend on the thickness of the AAO films, and on the interpore distance (pore density). Furthermore, a strong dependence of the reflectance on the anodization electrolyte was found in the UV region, due to the trapping of different ions within the porous structure. The chemistry of the system therefore plays an important role regarding the optical properties. A statistical study was finally conducted to obtain a relation between the maximum reflectance and the morphological parameters of the AAO films. A linear regression for estimating the maximum reflectance is proposed, where the influence of the interpore distance was found to be more significant than that of the film thickness.